Applicability of the decomposed theory of planned behavior for the evaluation of community-dwelling older adults’ acceptance in continuous usage of robot-assisted board games for cognitive training - Chiu-Mieh Huang; Su-Fei Huang; Yu-Ting Chen; Ching-Hao Chang; Hsiu-Chun Chien; Ying-Jie Chang; Kuei-Yu Huang; Jong-Long Guo (Digital Health)
Background Improving cognitive function in healthy older adults is a global concern. Cognitive training delays mental deterioration. The utilization of robots and board games for aiding older adults in cognitive training represents a prominent technological trend and is a subject of meriting investigation. Objective This study evaluates the acceptability and factors influencing the continuous usage intention of a robot-assisted board game (RABG) for cognitive training in community-dwelling older adults based on the decomposed theory of planned behavior (DTPB). Methods In this explanatory study, we developed an RABG with six educational modules. The experiences of 126 older adults recruited from northern Taiwan who completed the program were assessed using a DTPB-based questionnaire. Partial least-squares structural equation modeling was used to examine the correlations. Results The results demonstrate the DTPB's sufficient fitness and 79.9% explanatory power for the continuous usage intention of the RABG, confirming the effectiveness of the proposed structural model. Perceived usefulness positively affected attitude and continuous usage intention, indicating that perceived usefulness is critical in promoting older adults’ continuous usage intention. The interpersonal influence was a major antecedent of subjective norms. Self-efficacy affects perceived behavioral control. Attitudes and perceived behavioral control affected users’ intentions to use the RABG. Conclusions Our findings support the applicability of the DTPB in evaluating RABGs for cognitive training in older adults, suggesting its potential integration in future interventions.